PUBLIC MANAGEMENT REFORMS IN LITHUANIA: WHAT SHOULD REPLACE NEW PUBLIC MANAGEMENT AND WHY? - Nakrošis, Vitalis (Politologija, 2015)
This article analyses main public management doctrines (traditional administration, NPM and post-NPM), assesses the doctrinal basis of public management reforms in the 2004–2010 period, provides suggestions concerning principles, directions and process of future public management reforms in Lithuania. Despite different political views and terms of various Governments, important decisions of public management reforms were based on the party logic, whose purpose is to strengthen political authority of the government in office. The implementation of the ‘bureaucratic’ public administration strategy, whose content was informed by the ideas of post-NPM, was initially unsuccessful because of limited political ownership and the legalistic approach. The XV Lithuanian Government undertook wide public management reforms based on the managerial doctrine with prevailing NPM characteristics. A mix of the party logic and the NPM doctrine could be contradictory and risky in Central and Eastern European countries. Also, the NPM has not yielded good results in Continental Europe, its solutions do not match Lithuania’s problems and there is no solid empirical evidence about its effectiveness in Lithuania. Therefore, its application should be limited and selective during Lithuania’s public management reforms. Post-NPM is the best doctrine for future public management reforms, whose implementation in Lithuania should be supported by broader political consensus, better inter-institutional cooperation and a more managerial implementation approach.